A light curve model of V2491 Cyg: Classical nova outburst on a cool and massive white dwarf. (1st July 2021) - Kato, Mariko; Saio, Hideyuki; Hachisu, Izumi
Abstract: The classical nova V2491 Cyg was once suggested to be a recurrent nova. We have broadly reproduced the light curve of V2491 Cyg by a nova outburst model on a cold 1.36 M ⊙ white dwarf (WD), which strongly suggests that V2491 Cyg is a classical nova outbursting on a cold very massive WD rather than a recurrent nova outbursting on a warmer WD like the recurrent nova RS Oph. In the long-term evolution of a cataclysmic binary, an accreting WD has settled to a thermal equilibrium state with the balance of gravitational energy release and neutrino loss. The central temperature of the WD is uniquely determined by the energy balance. The WD is hot (cold) for a high (low) mass accretion rate. We present the central temperatures, ignition masses, ignition radii, and recurrence periods for various WD masses and mass accretion rates. In a classical nova, which corresponds to a low mass accretion rate, the WD is cool and strongly degenerated and the ignition mass is large, which result in a strong nova outburst. In a recurrent nova, the WD is relatively warmer because of a high mass accretion rate and the outburst is relatively weaker. The gravitational energy release substantially contributes to the luminosity during the recurrent nova outbursts. We compare physical properties between classical novae and recurrent novae and discuss the essential differences between them.